2003
DOI: 10.1093/annonc/mdg345
|View full text |Cite
|
Sign up to set email alerts
|

A phase I–II study of weekly cisplatin and gemcitabine with concurrent radiotherapy in locally advanced cervical carcinoma

Abstract: The association of cisplatin and gemcitabine with concurrent radiotherapy is active and well-tolerated in untreated LACC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 13 publications
0
29
0
1
Order By: Relevance
“…3 Gemcitabine has been used in cervical cancers with good results both as a single agent and in combination with cisplatin concurrent with radiotherapy. [4][5][6][7][8][9][10][11][12][13][14] The aim of present study was to evaluate the toxicity and efficacy of concurrent weekly Gemcitabine against the widely accepted concurrent weekly cisplatin with standard convention radiotherapy in management of locally advanced cervical cancer.…”
Section: Introductionmentioning
confidence: 99%
“…3 Gemcitabine has been used in cervical cancers with good results both as a single agent and in combination with cisplatin concurrent with radiotherapy. [4][5][6][7][8][9][10][11][12][13][14] The aim of present study was to evaluate the toxicity and efficacy of concurrent weekly Gemcitabine against the widely accepted concurrent weekly cisplatin with standard convention radiotherapy in management of locally advanced cervical cancer.…”
Section: Introductionmentioning
confidence: 99%
“…However; previous study using weekly cisplatin 40mg/m 2 had reported ototoxicity in 10% 15 while nephrotoxicity occurred in 42.9% in a study using weekly combination of gemcitabine with this standard dose of cisplatin. 16 Among hematologic toxicity; anemia was the most common (35.5%) followed by thrombocytopenia (31%) then neutropenia (26.6%) with grade 3 in 4.4% and no grade 4 that comparable to finding by Umanzor et al 6 However; Zarba et al 5 recorded grade 4 neutropenia in 4%. Anemia was found in 50% of patients treated with gemcitabine 125mg/m 2 and cisplatin 40mg/m 2 .…”
Section: Discussionmentioning
confidence: 58%
“…[4][5][6] Gemcitabine is activated intracellulary by deoxycytidine kinase and is converted into two active metabolites gemcitabine diphosphate and triphosphate which target DNA and RNA. It is considered to be an attractive compound to combine with ionizing radiation for several reasons: 1) It may inhibit repair of the DNA damage caused by radiation leading to increased cell death; 2) It may induce cell redistribution causing cells to accumulate in more radiosensitive phase of cell cycle; 3) Increased the radiosensitvity of hypoxic cells due to tumor shrinkage.…”
Section: Introductionmentioning
confidence: 99%
“…However, even with the best results, the local recurrence is still high (around 19-24%). Zarba et al (2003), in a phase I-II study of weekly cisplatin and gemcitabine with concurrent radiotherapy in locally advanced cervical carcinoma, determined the MTD (Mean Toxic Dose) for gemcitabine to be 150mg/m 2 concurrent with cisplatin 40mg/m 2 every week and daily external radiotherapy. Furthermore, they recommended a phase II dose of gemcitabine at 125mg/m 2 plus cisplatin 40mg/m 2 weekly and external radiotherapy for locally advanced disease resulting in 36 patients showing an overall response of 97.3% with 88.8% of complete responses, 8.3% of partial responses and 2.7% of stable disease.…”
Section: Discussionmentioning
confidence: 99%